BERBASIS MASALAH (PROBLEM BASED LEARNING) DAN PENGARUHNYA TERHADAP HASIL BELAJAR IPS - Siti Sahara, Mhd Zulkifli Hasibuan, Rijal (JURNAL PENDIDIKAN IPS, 2026)
This study aims to describe the implementation of Problem Based Learning (PBL) and analyze its impact on the Social Studies learning outcomes of seventh-grade students at UPT SMP Negeri 38 Medan in the 2025/2026 academic year. The research employed a mixed-methods approach with a sequential exploratory design, in which qualitative data were obtained through observations, interviews, and documentation to illustrate the implementation of PBL, while quantitative data were collected through pretests and posttests. The data collection process was carried out systematically using procedures designed to ensure the objectivity of the findings, including the use of research instruments that had undergone content validation and reliability testing. All analyses were conducted by integrating qualitative and quantitative findings, resulting in a comprehensive depiction of the effectiveness of the applied learning model. The results indicate that PBL was implemented effectively through stages of problem identification, group collaboration, information searching, solution analysis, and presentation of results. Quantitatively, the students’ average scores increased from 58.3 (pretest) to 81.7 (posttest). The normality test confirmed that the data were normally distributed (p > 0.05), the homogeneity test showed homogeneous variance (p > 0.05), and the paired sample t-test revealed a significant difference between scores before and after the intervention (p < 0.001). These findings affirm that PBL has a positive effect on improving learning outcomes while also enhancing motivation, active engagement, and students’ critical thinking skills in Social Studies learning.